2014
DOI: 10.1002/lary.24862
|View full text |Cite
|
Sign up to set email alerts
|

The role of microbes in the pathogenesis of acute rhinosinusitis in young adults

Abstract: Nasal and paranasal H. influenzae coinfection during viral infection may modify the symptoms and the extent of sinonasal mucosal disease observed in CBCT scans already from the beginning of the ARS episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 29 publications
5
32
0
Order By: Relevance
“…Thirty‐nine patients (78%) had respiratory virus nucleic acid in their nasopharynx at enrolment . Twenty patients (40%) underwent a maxillary sinus aspiration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty‐nine patients (78%) had respiratory virus nucleic acid in their nasopharynx at enrolment . Twenty patients (40%) underwent a maxillary sinus aspiration.…”
Section: Resultsmentioning
confidence: 99%
“…Background information was collected at enrolment, and a viral polymerase chain reaction was taken from the nasopharynx as described previously . The presence of nasal symptoms was recorded in symptom diaries .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the recovery of viral agents from the nose in the setting of ARS has ranged from 27% to 84%, this may reflect the variability and limitations of the specific techniques used. 23,[122][123][124] Inoculation of rhinovirus in humans produced greater than a 90% infection rate with up to 74% displaying ARS symptoms. 125,126 It has been hypothesized that a preceding AVRS may be associated with subsequent ABRS by inhibition of mucociliary clearance (MCC) and blockade of sinus ostia due to local swelling.…”
Section: Vb Ars: Pathophysiologymentioning
confidence: 99%
“…132,133 For these reasons, studies that directly sample the sinuses during an infection are needed. Autio et al 124 found that up to 84% of patients presenting with ABRS had viral nucleic acid detected during the early phase of the disease (days 2 to 3), and a coinfection with bacteria (56%) during the viral infection was found to correlate with worse disease scores.…”
Section: Vb Ars: Pathophysiologymentioning
confidence: 99%